Physicochemical And Sensory Properties of Sponge Cake Mocaf Enriched in Legume Flour: Sifat Fisikokimia Dan Sensoris Sponge Cake Mocaf Yang Diperkaya Tepung Kacang-Kacangan - Almira Bhadra Reyhannissa; Yannie Asrie Widanti; Akhmad Mustofa (Fakultas Sains dan Teknologi Unisri, 2024)
Mocaf (Modified Cassava Flour) is one type of flour processed local cassava food that is expected to replace wheat flour. Legume flour can be used as a source of protein while enriching the nutritional value of gluten-free cakes. This study aims to make a cake formulation with mocaf flour ingredients fortificated with high-protein legume flour. The study used a two-factor complete randomized design (RAL) with two repeats. Factors used are the comparison of mocaf flour and legume flour (40:60, 50:50, 60:40) as well as variations in the type of legume flour (green beans, kidney beans, soybeans). The best formulation produced by sponge cake with the highest protein content is in the treatment ratio of 40:60 mocaf flour and composite flour with green bean flour types, namely water content 22.65%, ash content 1.38%, fat content 10.65%, protein content 7.28%, carbohydrate content 56.72%, and fiber content 8.32%. Organoleptic tests included 2.46 (dark green), mocaf flavor 2.55 (not too pronounced), legumous flavor 3.29 (slightly flavored), soft texture 2.53 (not too soft), soft texture 2.93 (slightly tender), aftertaste 2.80 (slightly concentrated), off flavor 2.62 (not too deviated), preferred value 2.85 (slightly preferred) and physical development volume expanded by 16.55%.